Two recipes for repelling hot water - Timothée Mouterde (Nature Portfolio, 2019)
It has previously been reported that hot drops impacting on a colder surface can lead to loss of surface hydrophobicity unless the surface features are very small. Here the authors find that both small and large features but not intermediate ones are able to preserve hydrophobicity.